Quality of life and quality of education among physiotherapy students in Europe - Schramlová, Michaela; Řasová, Kamila; Jonsdottir, Johanna; Pavlíková, Markéta; Rambousková, Jolana; Äijö, Marja; Šlachtová, Martina; Kobesová, Alena; Žiaková, Elena; Kahraman, Turhan; Pavlů, Dagmar; Bermejo-Gil, Beatriz María; et al. (Frontiers in Medicine, 2024)
The study of physiotherapy is challenging and can affect the students' well-being and quality of life. The aim of this study was to describe and compare factors that could affect well-being among students across Europe. Methods In this descriptive cross-sectional study using an online questionnaire survey, students of bachelor's physiotherapy programs from 23 European faculties, from 8 countries, were interviewed on mental health and stress burden, sleep quality, dietary habits, and physical activity.Although 75% of students rated their quality of life positively and 47% were satisfied with their mental health, 65% showed higher levels of stress and 51% described impaired sleep quality. The minimum physical activity of 150 minutes weekly was described by 79% of students, within which 67% engaged in strengthening twice a week. Students with a higher stress load/worse psychological health also showed worse sleep quality and lower amount of physical activity, women were significantly worse off. In terms of physical activity and sleep quality, students from Finland and Kosovo achieved the best results, while students from Italy, Greece, and Portugal achieved the worst. Students from Italy indicated the greatest dissatisfaction with the organization of the study system and communication with teachers, while in Kosovo students rated the communication and study organization the highest. All students had a problem with adhering to nutritional habits. Students from Italy and Spain, with the lowest body mass indexes and weight averages, were closest to the nutrition recommendations.We demonstrated that physiotherapy students are burdened with stress, suffer from sleep disorders, and do not follow the recommendations regarding nutrition nor physical activity. There are significant differences between universities and countries in some aspects.